High sustained virologic response rate after 8 weeks of direct-acting antivirals in cancer patients with chronic hepatitis C virus. Issue 10 (24th August 2022) - Yibirin, Marcel; Hosry, Jeff; Yepez Guevara, Eduardo; Granwehr, Bruno P.; Jiang, Ying; Mustafayev, Khalis; Angelidakis, Georgios; Torres, Harrys A.
Abstract : Objective: There is no prospective data on 8 weeks of direct-acting antivirals (DAA) therapy with glecaprevir/pibrentasvir (GLE/PIB) or ledipasvir/sofosbuvir (LDV/SOF) in hepatitis C virus (HCV)-infected patients with different types of malignancies. This study evaluated the efficacy and safety with 8 weeks of DAA therapy in cancer patients with chronic HCV infection. Methods: Patients treated with DAAs at our center during 2014–2021 were included in a prospective observational study. Efficacy (sustained virologic response at 12 weeks; SVR12) and safety [adverse events and clinically significant drug-drug interactions (DDIs)] were assessed. Results: We included 47 patients. Most were men (29; 62%), white (33; 70%), non-cirrhotic (45; 96%), and with HCV genotype 1 (38; 85%). None of the patients had HCC. The SVR12 rate was 96% (45/47; 95% CI: 86–99%) for the entire study cohort, 100% [17/17; 95% CI: 82–100%] for the patients treated with GLE/PIB and 93% [28/30; 95% CI: 79–98%] for the patients treated with LDV/SOF. Fisher's exact test showed no significant difference in SVR12 rates between the regimens ( P = 0.53). No patients had serious adverse events (grade 3–4) or treatment discontinuation. Among the 17 patients who received concomitant cancer therapy, no DDIs occurred. Conclusion: Eight weeks of DAA therapy is highly effective and safe in HCV-infected patients with different types of malignancies and may grant access to investigational cancer therapy, broadening treatment options.